Intergenerational communication in song “Saat Kau Telah Mengerti” with Hjelmslev’s semiotic perspective - Jennifer Susanto; Flavianus Nanda Harsono; Rustono Farady Marta; Hana Rochani Gustasari Panggabean; Beby Chandra Wijaya (International Journal of Visual and Performing Arts, 2024)
The song “Saat Kau Telah Mengerti” (lit. “When You Have Understood”), recorded by Virgoun, was streamed over a million times on YouTube when it was released in January last year and has been circulated in various edited versions on various online platforms. The lyrics present messages of hopes and wishes from parents to their children, thus touching the hearts of its listeners. Through the song's music, lyrics, and video clips, the objective of this research is to interpret and explore the meaning of parents' communication with their children. This study focuses its research question on elements utilized in the lyrics, music, and video clips of the song. This research analysis uses a qualitative approach with an interpretative paradigm based on Louis Hjelmslev's semiotic method and the validity test, which will be achieved through triangulation. Through Hjelmslev's semiotic research on forms and substance of expression and content, this research found that a communication gap exists between parents and their children. The gap stems from the generational differences between fathers and daughters, which this song seeks to bridge by encouraging the child to empathize with the parents. The actions of parents who strive for their children's benefit can occasionally be misinterpreted by their children as something negative. Based on the results, the study recommends music as an effective tool for conveying messages to mitigate parent-child communication gap